Peran Sosial Media Terhadap Perilaku Mahasiswa FKG UMSurabaya dalam Menjaga Kesehatan Rongga Mulut: The Role of Social Media on the Oral Health Maintenance Behaviour of FKG UMSurabaya Students - Melati, Bingah; Nerito, Prima; Musmarihan, Angeline (Fakultas Kedokteran Gigi IIK Bhakti Wiyata, Kediri., 2025)
The incidence of dental caries is still high in almost all populations in Indonesia. Continues efforts are needed to improve oral health status, one of which is education through social media. The author wants to know the effect of social media on student’s oral health care behavior. This quantitative study involved 23 FKG UMSurabaya based on non-probability sampling method with purposive sampling type with descriptive observational study and cross-sectional design. Data was collected through a survey using questionnaire. The results showed that respondents used a combination of several social media (95,65%) to find information about oral health. Tiktok is the most used platform (47,83%). A total of 56,52% of respondent used the Halodoc health service platform to access information, get advice, buy medicines or make appointment with a doctor. This shows that students are already able to identify information before it is later disseminated directly or through social media, which can potentially improve the oral health of the community.